Effects of the three-point rule in German amateur football - Alexander Dilger; Gerrit Froböse (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2018)
Possible effects of the introduction of the three-point rule in 1995 are tested by using data from amateur football leagues in Germany, concretely in Westphalia. There are as expected signifi-cantly less draws and more goals since the rule change. For even amateurs follow incentives. – – Mögliche Effekte der Einführung der Drei-Punkte-Regel im Jahr 1995 werden getestet mit Da-ten aus Amateurfußballligen in Deutschland, konkret in Westfalen. Es gibt erwartungsgemäß signifikant weniger Unentschieden und mehr Tore seit der Regeländerung. Denn auch Amateure folgen Anreizen.
Keywords: L83; Z20; Z28; 650